Contact investigation of tuberculosis in Brunei Darussalam: Evaluation and risk factor analysis. Issue 1 (23rd June 2022) - Chaw, Liling; Abdul Hamid, Rafizah; Koh, Kai Shing; Thu, Kyaw
Abstract : Introduction: We evaluated the yield of tuberculosis (TB) contact investigation in Brunei Darussalam, and identified the associated factors for latent TB infection (LTBI) diagnosis, as well as for initiating and completing LTBI treatment. Methods: Data were extracted and digitalised for all close contacts of pulmonary TB (PTB) cases at the National TB Coordinating Centre from January 2009 to December 2018. Generalising estimating equations logistic regression models were used to determine the associated factors. Manual matching against electronic health records system was done to identify contacts who had progressed to active TB disease. Results: Among 10 537 contacts, 9.9% (n=1047) were diagnosed as LTBI, out of which 43.0% (n=450) initiated LTBI treatment. Among those who initiated, 74.0% (n=333) completed LTBI treatment. Contact factors associated with LTBI diagnosis include being male (adjusted OR (aOR)=1.18 (95% CI 1.03 to 1.34)), local (aOR=0.70 (95% CI 0.56 to 0.88)) and a household contact (aOR=1.59 (95% CI 1.26 to 1.99)). Contacts of index cases who were <60 years old and diagnosed as smear positive PTB (aOR=1.62 (95% CI 1.19 to 2.20)) had higher odds of being diagnosed with LTBI. Local LTBI cases had higher odds of initiating LTBI treatment (aOR=1.86 (95% CI 1.26 to 2.73)). Also, LTBI cases detected from local (aOR=2.32 (95% CI 1.08 to 4.97)) and smear positive PTB index cases (aOR=2.23 (95% CI 1.09 to 4.55)) had higher odds of completing LTBI treatment. Among 1047 LTBI cases, 5 (0.5%) had progressed to active PTB within 1–8 years post-LTBI diagnosis. Discussion: LTBI burden is disproportionately high towards foreign nationals, with higher odds of LTBI diagnosis but lower odds of treatment initiation. Determining the reasons of not initiating LTBI treatment will be useful to help improve LTBI treatment uptake. Establishing digital databases and building TB laboratory capacity for molecular typing would be useful to determine the contribution of LTBI or reactivation towards TB incidence in Brunei.